-y+42-3y=6

Simple and best practice solution for -y+42-3y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -y+42-3y=6 equation:


Simplifying
-1y + 42 + -3y = 6

Reorder the terms:
42 + -1y + -3y = 6

Combine like terms: -1y + -3y = -4y
42 + -4y = 6

Solving
42 + -4y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + -4y = 6 + -42

Combine like terms: 42 + -42 = 0
0 + -4y = 6 + -42
-4y = 6 + -42

Combine like terms: 6 + -42 = -36
-4y = -36

Divide each side by '-4'.
y = 9

Simplifying
y = 9

See similar equations:

| (2p-1)(p+3)-(7p+4)(p+3)= | | 1/3-4=-y | | 3=3(2x-4)-3(4x+4)-10 | | 36r^2-121= | | ln(6)+ln(x)=ln(6x) | | 42a^2+a-30=0 | | 6a^2-28a+16= | | 28/5 | | 36=b(5)(6) | | (B/9)-.5=(5/18) | | (x)(-3)-4=-10 | | 81x+36x+20=0 | | (3x^-5/8y^-7)^-2 | | 0=20t-5(t^2)+25 | | 4x-3/8 | | 6x-2x+7=x-2+9 | | 5x+6=30+x | | 30xm+15xn-20ym-10yn= | | 25x^4-81y^2=0 | | 1/4x=x-33 | | 5-(-3)+6= | | f(x)=-4x^2+16x-5 | | x/(36x^2-9) | | x+2x+5x=32 | | x^2+14xy+24y=0 | | 5+4ln(x)=7 | | x/36x^2-9 | | m^2+22m-4=0 | | y^4-6y^3+12y^2-10y+3= | | a=-1e+-1s+-1y | | w^2-13w+42.25=0 | | 1/4x^4-9/25=0 |

Equations solver categories